Effects of Breaking Up Prolonged Sitting on Cardiovascular Parameters: A systematic Review - da Silva, Gustavo Oliveira; Santini, Luiza Batista; Farah, Breno Quintella; Germano-Soares, Antonio Henrique; Correia, Mariliade Almeida; Ritti-Dias, Raphael Mendes (International Journal of Sports Medicine, 2021)
The aim of this systematic review was to analyze the acute and chronic effects of sitting breaks on cardiovascular parameters. PubMed and Web of Science databases were searched by two independent researchers for relevant studies published until February 2020. Acute or chronic studies reporting the effects of sitting breaks or reduction in sitting time on cardiovascular parameters were examined. The eligibility criteria followed PICOS: Population - Humans ≥ 18 years old; Interventions – Sitting break strategies; Comparisons – Uninterrupted sitting; Outcomes – Cardiovascular parameters (blood pressure, heart rate, ambulatory blood pressure, vascular function, pulse-wave velocity, cerebral blood flow and biomarkers); Study design – Randomized controlled trials, non-randomized non-controlled trials and randomized crossover trials. Forty-five studies were included, where 35 investigated the acute and 10 the chronic effects of sitting breaks or reductions in sitting time. Walking was the main acute study strategy, used in different volumes (1 min 30 s to 30 min), intensities (light to vigorous) and frequencies (every 20 min to every 2 h). Acute studies found improvements on cardiovascular parameters, especially blood pressure, flow-mediated dilation, and biomarkers, whereas chronic studies found improvements mostly on blood pressure. Breaking up or reducing sitting time improves cardiovascular parameters, especially with walking.
Keywords: sitting breaks, cardiovascular health, physical activity